SAND AS A SOIL STABILIZER - Kollaros, G.; Athanasopoulou, A. (Bulletin of the Geological Society of Greece, 2016)
Clayey soils often exhibit undesirable engineering behaviour such as low strength, swelling and shrinkage characteristics etc. To improve these properties, the common method followed is stabilization. An experimental program carried out in this study aims to highlight the physical mechanisms of stabilization of an expansive soil by adding an inert material (sand). The study aimed to analyze the effect of stabilization on the variation of soil consistency and the results have shown that soil consistency improved appreciably. The findings of the laboratory testing procedures also presented substantial improvement in strength with the addition of sand percentages up to 60% by weight of soil, as well a noticeable alteration in the moisture-density relation. The soil tested could be used as subgrade material in pavement structures for low volume bearing roads, after its stabilization with fine sand. A further step in the investigation process could be the analysis of the swelling potential of clayey soils in conjunction with the addition of other waste materials along with sand, as well as the cost-benefit relationships of stabilization with sand in large projects like the highway construction.